ANALISIS KONTRIBUSI RETRIBUSI PEMERIKSAAN MUTU DAN SERTIFIKASI HASIL PERIKANAN TERHADAP PENDAPATAN ASLI DAERAH PROVINSI MALUKU - Samie Lambert Jacobs, Victor Pattiasina, (IQTISHODUNA, 2010)
This Study aim to analyze inspection contribution quality of and fishery certification to Original Earnings of Area Town Maluku. Result of calculation, shown that regression coefessien inspection retribution quality of and certification result of fishery to original earnings area in Town Maluku equal to its 0,806 meaning if inspection retribution quality of and certification result of fishery increase/mounting equal to 1% hence growth fishery retribution will mount equal to 80,6 %. This study use obtained second data from Statistical Bureau Center Town Maluku. Data hereinafter analysis by using quantitative Analysis by using regression method and also verification examination of proven hypothesis that there are influence inspection retribution quality of and certification result of fishery to growth original earnings are.